A cross-sectional study on utilization of maternal health services and its determinants among rural population of district Sitapur, Uttar Pradesh - Neyaz, Arslan; Chaubey, Jaideep K.; Ahmed, Malik S.; Kumar, Virendra; Nayak, Kripashankar (International Journal Of Community Medicine And Public Health, 2021)
Background: In India, despite substantial improvements in maternal health over the last decade or so, still condition is even poor in rural areas. As per National health policy 2017, target is to reduce MMR to 100 by 2020 and sustaining antenatal coverage at 100%, institutional delivery 80% and skilled attendance of birth 100% by 2025.The study is conducted with the objective to assess the pattern of maternal health service utilization and to identify the factors affecting it. Methods: A community based cross-sectional study was conducted at field practice area of Rural Health Training Centre, Hind Institute Of Medical Sciences, Sitapur with a sample of 208 women selected using systematic random sampling. SPSS Statistics 20.0 was used for data entry and calculation of statistical tests. Results: ANC utilization was found to be 70.7% whereas minimum recommended ANC visits were 50%. Only 54.8% deliveries were found to be institutional whereas 59.1% women received at least one postnatal check-up in our study. Most common reason for not utilizing ANC, Institutional delivery and PNC services was found to be tradition, availability of trained person and no need respectively. A highly significant association was found between maternal health service utilization and woman’s education, partner’s education, partner’s occupation, birth order and standard of living index (p<0.05). Conclusions: This study established that educating the population, empowering women, promoting maternal health service utilization in multipara’s and improving the socio-economic status of the family would yield greater results in increasing the use of maternal health services.